Comparing Microwave and Classical Synthesis of Oxymethylene Dimethyl Ethers. Issue 14 (12th May 2022) - Endres, Patrick; Zechel, Stefan; Winter, Andreas; Hager, Martin D.; Schubert, Ulrich S.
Abstract: Polyoxymethylene dimethyl ethers (OME n ) are considered as substituents or additives for fossil diesel fuel. Efficiency of the synthesis is crucial for the development of industrial scale production plants. Therefore, the design of suitable catalysts and the efficient heating play important roles in OME fuel synthesis. In this work, microwave‐assisted synthesis (MAS) is carried out and compared to a classical approach using standard thermal heating. Different polymeric materials, e.g., Amerlyst15, are utilized as catalysts, and screened for the catalytic synthesis of OME. Within this approach, the kinetics of the reaction are analyzed in detail. Abstract : Microwave‐assisted heating is applied and evaluated in terms of polymer catalyzed OME fuel synthesis. In this context, the effect of temperature, time, and type of polymeric catalyst on the product distribution and side‐product formation is studied. Furthermore, an acceleration of the reaction speed using microwave‐assisted heating is obtained.